Isolated absence of F waves and proximal axonal dysfunction in Guillain-Barré syndrome with antiganglioside antibodies. Issue 2 (1st February 2000) - Kuwabara, S; Ogawara, K; Mizobuchi, K; Koga, M; Mori, M; Hattori, T; Yuki, N
Abstract : OBJECTIVES: To investigate the pathophysiology of selective absence of F waves and its relation with antiganglioside antibodies in Guillain-Barré syndrome (GBS). Some patients with GBS show the absence of F waves as an isolated conduction abnormality, which has been interpreted as demyelination in the proximal nerve segments. METHODS: In 62 consecutive patients with GBS, sequential nerve conduction and F wave studies were reviewed, and antibodies against ganglioside GM1, GM1b, GD1a, GalNAc-GD1a, GD1b, and GQ1b were measured by an enzyme linked immunosorbent assay. RESULTS: In the first electrophysiological studies, isolated absence of F waves was found in 12 (19%) patients. Sequential studies in 10 of these patients showed two electrophysiological sequel patterns; rapid restoration of F waves (six patients), and persistent absence of F waves with distal motor nerve degeneration (acute motor axonal neuropathy, four patients). None of the 10 patients showed evidence of demyelination in the proximal, intermediate, or distal nerve segments throughout the course. Of the 62 patients, IgG antibodies against GM1, GM1b, GalNAc-GD1a, or GD1b were significantly associated with the electrodiagnosis of acute motor axonal neuropathy, and patients with these antibodies more often had isolated absence of F waves than patients without them (11 of 36 (31%) v one of 26 (4%); p <0.01). Eleven of the 12 patients with isolated absence of F waves had positive serology for one or more antiganglioside antibodies. CONCLUSIONS: In GBS with antiganglioside antibodies, isolated absence of F waves is a frequent conduction abnormality especially in the early phase of the disease, and may be caused by axonal dysfunction, such as physiological conduction block or axonal degeneration at the nerve roots.